Health-Promoting Behaviors and Their Predictors Among Nurses in Saudi Arabia - Alreshidi, Nashi; Alrimali, Afaf Mufadhi (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2026)
Background: Nurses fulfill a critical dual role as both caregivers and health promoters; however, their own health-promoting behaviors (HPBs) frequently receive inadequate attention. These behaviors significantly influence nurses’ personal well-being, professional credibility, and willingness to advocate for healthy lifestyles among patients. In Saudi Arabia, empirical evidence regarding HPB levels and their demographic and occupational predictors among clinical nurses remains scarce, hindering the design of targeted wellness interventions.Purpose: This study evaluated the levels of HPB among clinical nurses in Saudi Arabia and identified significant demographic and occupational predictors.Methods: A cross-sectional study was conducted among 233 clinical nurses from 16 public hospitals using convenience sampling. Data were collected through an online, self-administered questionnaire that incorporated the Health-Promoting Lifestyle Profile II (HPLP-II) and items assessing perceived health status and sociodemographic characteristics. Data normality was assessed using Kolmogorov-Smirnov and Shapiro-Wilk tests. In addition to bivariate analyses (t-tests and ANOVA), multiple linear regression was performed to identify independent predictors while controlling for confounders.Results: The overall mean HPLP-II score was 2.46 ± 0.46, reflecting a moderate level of engagement in HPBs. Spiritual growth and interpersonal relations were the highest-scoring domains, whereas physical activity was the lowest. The regression model explained 24% of the variance (R² = 0.24). Multivariable analysis identified perceived health status (p < 0.001) and supervisory job titles (p = 0.046) as the only significant independent predictors of higher HPB scores. No other demographic or occupational characteristics were significant.Conclusion: Clinical nurses demonstrated a moderate level of HPBs, primarily driven by their perceived health status and occupational role. Strengthening nurses’ health perceptions through structured wellness initiatives, supported by nursing leadership, may enhance behavioral engagement and reinforce their effectiveness as health advocates.